The role of long intergenic noncoding RNA 00511 in malignant tumors: a meta-analysis, database validation and review. Issue 1 (1st January 2020) - Ding, Jianlong; Cao, Junyan; Chen, Zhaocong; He, Zhiming
ABSTRACT: Increasing studies suggested that long intergenic noncoding RNA 00511 (LINC00511) could facilitate the progression of various malignancies and correlates with prognosis of patients with malignant tumors. However, its clinical significance is still not completely clarified. Therefore, we performed a meta-analysis and bioinformatics analysis to further evaluate the correlation of LINC00511 expression level with prognosis and metastasis in patients with tumors. The pooled hazard ratio (HR) with 95% confidence interval (CI) was used to evaluate the prognostic significance of LINC00511 expression level. The pooled odds ratio (OR) with 95% CI was applied to assess the association between LINC00511 expression level and tumor metastasis. A total of 12 studies involving 1040 tumor patients were included in this meta-analysis. The pooled analyses suggested that higher LINC00511 expression level correlated with worse overall survival (OS) (HR = 1.93, 95% CI 1.49–2.49, P < 0.001) and higher incidence of lymph node metastasis (OR = 3.07, 95% CI 2.23–4.23, P < 0.001). Additionally, bioinformatics analysis based on TCGA datasets also showed that increased LINC00511 expression level may predict poor OS and disease-free survival (DFS) in patients with malignant tumors. Taken together, our finding suggested that high LINC00511 expression level may be correlated with poor prognosis and high incidence of metastasis. Nevertheless, further large-scale and high-quality studies are needed to validate our findings. Graphical Abstract: .